Analyzing Persistent State Interactions to Improve State Management - Kiciman, Emre; Daniels, Brad; Lu, Shan; Roussev, Roussi; Wang, Yi-Min; Verbowski, Chad; Lee, Juhan (ACM SIGMETRICS 2006, 2006)
A primary challenge to building reliable and secure computer systems is managing the persistent state (PS) of the system: all the executable files, configuration settings and other data that govern how a system functions. The difficulty comes from the sheer volume of this persistent state, the frequency of changes to it, and the variety of workloads and requirements that require customization of persistent state. The cost of not managing a are the leading cause of downtime at Internet services, troubleshooting configuration problems is a leading component of total cost of ownership in corporate environments, and malware effectively, unwanted persistent state²is a serious privacy and security concern on personal computers.
Short Paper.